The Professional Ethics Performance of Teachers in Basic Educational Institutions under the Office of Surin Primary Educational Service Area 3 - Yodnongthum, Wisawakorn; Sangngern, Supod; Suriyasookpasert, Pichai; Narunakboonsup, Pinpinut; Somboonmak, Chayasara (Rajapark Journal, 2024)
The objectives of this research are: 1) Study the professional ethics performance of teachers in basic educational institutions under the office of Surin Primary Educational Service Area 3. 2) Compare teachers’ practices in following the teaching professional code of ethics, classified by gender and academic status. 3) Study guidelines for promoting work performance according to teaching professional standards and teaching professional ethics. A sample group of 348 teachers was determined using Crezzi and Morgan tabulation and stratified random sampling. Proportionally, the data collection tool is a questionnaire. Data were analyzed using statistics: percentage, mean, and standard deviation. The research results found that 1) compliance with the teaching professional code of ethics is high in every aspect. It was found that the aspect with the highest average was ethics for professional associates, and the aspect with the lowest average value was social ethics. 2) The results of comparing the practices of teaching professional ethics classified by gender found that overall and in each aspect, they were not different. Classified by academic status, it was found that overall and in each aspect, they are significantly different at the .05 level. 3) Target group analysis results by triangulating showed that 1) on ethics towards oneself, the emphasis is placed on teachers developing themselves to have standards in their work. 2) On the ethics of the profession, the emphasis is placed on performance evaluation. 3) Ethics towards service recipients emphasizes improving the service system to be efficient. 4) The ethical standard for professional co-operators is that administrators adhere to the principles of fairness in management. 5) Ethics for society focus on participating in activities and giving opportunities for the community to participate in management to build strength in educational institution administration.